TIC Dans L’enseignement Des Mathematiques Au Lycee Marocain - Harraq, Jamal; Hattaf, Khalid; Bamhamed, Mohamed; Achtaich, Naceur (European Scientific Journal, ESJ, 2018)
In this work, we investigate the use of information and communication technologies (ICT) in the teaching of mathematics at Moroccan high school. We first start with the analysis of school books from the three years of Baccalaureate. Furthermore, we analyze the pedagogical orientations concerning the use of these technologies. The results obtained from this study show that the use of ICT in mathematics education at Moroccan high school is still too limited.